OLAHRAGA DAN IDENTITAS NASIONAL: PENCAK SILAT DI INDONESIA TAHUN 1950-1970 - , Aulia Rahman, S.Hum., Dr. Sri Margana M. Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
At the beginning of 1950, Indonesia began developing new national identity based on cultures. Cultures rooted origin from Indonesia were brought out to the society and introduced as media in new identity development. This new identity was expected to be the centre of the attention about indonesia for other countries. But above all else, the goodness in the cultures were expected to blend in with the Indonesian society and could be implemented in their daily lives. The main topic discussed in this research is 'The problems in forming national identity through sports and cultures'. The main questions in this topic are: Why 'pencak silat' was chosen to build and form the national identity and how is the forming process? How could 'pencak silat' as traditional art be integrated into national sport? C Sources for this research as in the form of files were taken from 'Arsip Nasional' and Padepokan Pencak Silat, Taman Mini, Jakarta. More over there were Government Regulations, National Papers, printed articles and books related to the theme of the research. ultures politicalization medium. In this research, founded some important facts. First important fact, unique characterized tradition could be used as one country's. Second important fact, tradition could be brought into national stage with slight modifications. Third important fact, Sport event is the new chapter of competitions among countries. This research conclued, Indonesia needs national identity that it supported by local values. Pencak silat is one element culture and sport that completes criteria to build the national identity. The process such as with integration âpencak silatâ within branch of national sport and competited on international competition.